Identifikasi Penggunaan Lahan Perumahan Bukit Indah Permai Kota Samarinda dengan Menggunakan Orthophoto - Artanti Tustika; Dawamul Arifin; Radik Khairil Insanu; Nia Kurniadin (P3KM Politani Samarinda, 2023)
Land use according to the Basic Agrarian Law is the structure and pattern of land use, whether planned or not, which includes land supply, land allotment, land use, and maintenance. Land use is regulated to meet activities. Sustainable social and livelihood activities result in the amount of land needed, type, and location. Land use arrangements determine social accessibility, economic opportunity, movement patterns, and survival. Bids to change land use patterns should take into account the problems that will arise as a result of land use reforms. Land use information will be able to be used as data/information in making decisions on the development planning of an area. Bukit Indah Permai housing is one of the housing areas in the Samarinda which offers several types of housing, like types 21, 27, 36, and type 45. Land use information from the Bukit Indah Permai housing area will be able to provide consideration for potential consumers to make Bukit Indah Permai housing the residence of their choice. From the results of ortho data processing, it can be seen that land use in Bukit Indah Indah housing includes housing, green open spaces, public facilities (roads), and social facilities. Each of these land uses has a different area, namely for the area of ​​land use as housing is 50.57%, land use as green open space covers an area of ​​32.3%, land use for social and public facilities (road) respectively - 3.65% and 13.48%.